Concept art for 2D animation film adaptation of short story Colorful Mind - Putra, Juliana Suhindro; Yosela, Suksan; Laurencia, Jessica (Universitas Indraprasta PGRI, 2024)
The concept of short story titled 'Colorful Mind' is written in the third person. Its plot was inspired by the fact that education still prioritizes logic over all else and hence dismisses creative thinking. This stigma drives children to choose logic-based academic disciplines over creative subjects, even if this is not their true calling. Using this issue as the story's moral, the production of the film 'Colorful Mind' intends to encourage children of this generation to pursue their love and calling for art without getting swayed by society's old-fashioned stigma. The concept art for 'Colorful Mind' hopes to communicate successfully to its viewers through its visual features by employing solid research and theories, so that the message of the story may be easily grasped to its target of 7-8-year-old children.